Microstructural and Mechanical Properties of Al‐Based Composites Reinforced with In‐Situ and Ex‐Situ Al2O3 Nanoparticles1. Issue 4 (16th September 2015) - Casati, Riccardo; Fabrizi, Alberto; Timelli, Giulio; Tuissi, Ausonio; Vedani, Maurizio
Abstract : A powder metallurgy route based on high‐energy ball milling and powder consolidation by ECAP is used to produce Al‐matrix composites reinforced with Al2 O3 nanoparticles. The reinforcement is produced in‐situ during the milling process and added ex‐situ. Ball milling led to the fragmentation of the oxide layer that covers the Al particles and to the formation of very thin Al2 O3 dispersoids. Moreover, it was able to break the Al2 O3 particle clusters added ex‐situ and to embed the oxide in the ductile Al matrix. After powder consolidation by ECAP, the nanocomposites showed an ultra‐fine grained and fully dense matrix characterized by uniformly dispersed nanoparticles. Abstract : Ball milling breaks the native oxide layer that covers the Al particles and the alumina clusters added ex‐situ. It is also responsible for the embedding of the oxide particles in the ductile Al matrix. ECAP is used to consolidate the nanocomposite powders into high strength bulk materials.